2017
DOI: 10.3390/cancers9100142
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelet-Derived ADP and ATP in Promoting Pancreatic Cancer Cell Survival and Gemcitabine Resistance

Abstract: Platelets have been demonstrated to be vital in cancer epithelial-mesenchymal transition (EMT), an important step in metastasis. Markers of EMT are associated with chemotherapy resistance. However, the association between the development of chemoresistance, EMT, and the contribution of platelets to the process, is still unclear. Here we report that platelets regulate the expression of (1) human equilibrative nucleoside transporter 1 (hENT1) and (2) cytidine deaminase (CDD), markers of gemcitabine resistance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 87 publications
(101 reference statements)
0
27
0
1
Order By: Relevance
“…Platelet releasates, induced by the agonists of the thrombin receptors, protease activated receptor-1 (PAR1) and PAR4 [ 37 ], promote the proliferation of MCF-7 and MDA-MB-231 breast cancer cells and angiogenesis via the phosphoinositide 3-kinase/protein kinase C (PI3K/PKC) pathway [ 38 ]. Platelet activation induced by other agonists, including the adenosine diphosphate (ADP) (through its receptor P2Y12 and P2Y1) also promotes tumor growth in ovarian cancer and pancreatic cancer [ 39 , 40 ]. Recently, the relationship between P2Y12 and cancer was reviewed by Ballerini et al indicating the important role of P2Y12 in malignant cells [ 41 ].…”
Section: Roles Of Platelets In Cancer Development and Progressionmentioning
confidence: 99%
“…Platelet releasates, induced by the agonists of the thrombin receptors, protease activated receptor-1 (PAR1) and PAR4 [ 37 ], promote the proliferation of MCF-7 and MDA-MB-231 breast cancer cells and angiogenesis via the phosphoinositide 3-kinase/protein kinase C (PI3K/PKC) pathway [ 38 ]. Platelet activation induced by other agonists, including the adenosine diphosphate (ADP) (through its receptor P2Y12 and P2Y1) also promotes tumor growth in ovarian cancer and pancreatic cancer [ 39 , 40 ]. Recently, the relationship between P2Y12 and cancer was reviewed by Ballerini et al indicating the important role of P2Y12 in malignant cells [ 41 ].…”
Section: Roles Of Platelets In Cancer Development and Progressionmentioning
confidence: 99%
“…Previous studies have indicated that P2 signalling promotes cancer invasion and chemotherapy resistance by supporting EMT in cancer cells [45]. Signalling through ATP, for example, can promote the upregulation of the mesenchymal transcriptional factor SNAIL1 in prostate cancer cells [46], whereas we previously demonstrated that ADP signalling promotes SLUG upregulation in PDAC cells [9]. SNAIL1 and SLUG (SNAIL2) belong to a family of mesenchymal transcriptional factors that can modulate EMT and chemotherapy resistance through controlling the expression of cell adhesion proteins (e.g., E-cadherin), other mesenchymal transcriptional factors (e.g., ZEB1) or drug metabolising enzymes and drug transporter proteins (e.g., CDD, ENT1) [5].…”
Section: Discussionmentioning
confidence: 70%
“…However, its short-term activity and recent FDA approval of a reversal agent may make it a more favourable choice than other antiplatelet agents in the context of cancer-associated thrombosis [5]. It is important to mention that several clinical trials failed to show a survival benefit of using anticoagulants for the primary or secondary prevention of venous thrombosis in pancreatic cancer, despite a reduction in the incidence of thrombotic events at the expense of the bleeding risk [6][7][8][9]. Therefore, antiplatelet medication, such as ticagrelor, may provide an alternative strategy to mitigate cancer-associated thrombosis, as well as conferring a direct anti-tumour activity, as highlighted by our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations